2014
DOI: 10.4161/auto.29309
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus NSP6 restricts autophagosome expansion

Abstract: Autophagy is a cellular response to starvation that generates autophagosomes to carry long-lived proteins and cellular organelles to lysosomes for degradation. Activation of autophagy by viruses can provide an innate defense against infection, and for (+) strand RNA viruses autophagosomes can facilitate assembly of replicase proteins. We demonstrated that nonstructural protein (NSP) 6 of the avian coronavirus, infectious bronchitis virus (IBV), generates autophagosomes from the ER. A statistical analysis of MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
231
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(246 citation statements)
references
References 39 publications
7
231
1
1
Order By: Relevance
“…The authors conclude that the presence of exogenous, individually expressed IBV nsp6, which localizes to the ER, induces the formation of autophagosomes in contrast to other IBV replicase proteins. Additionally, although autophagosomes induced by IBV nsp6 or IBV infection appeared smaller than conventional autophagosomes observed after starvation of cells, they were similar in size to DMVs (Cottam et al, 2014). However, the data reported here do not appear to support the assumption that there is a functional link between IBV nsp6 and autophagosomes, and a role of the autophagy in the formation of IBV replicative structures can hereby not be demonstrated.…”
Section: Virus-host Interactionscontrasting
confidence: 91%
See 1 more Smart Citation
“…The authors conclude that the presence of exogenous, individually expressed IBV nsp6, which localizes to the ER, induces the formation of autophagosomes in contrast to other IBV replicase proteins. Additionally, although autophagosomes induced by IBV nsp6 or IBV infection appeared smaller than conventional autophagosomes observed after starvation of cells, they were similar in size to DMVs (Cottam et al, 2014). However, the data reported here do not appear to support the assumption that there is a functional link between IBV nsp6 and autophagosomes, and a role of the autophagy in the formation of IBV replicative structures can hereby not be demonstrated.…”
Section: Virus-host Interactionscontrasting
confidence: 91%
“…TM3 largely consists of transmembrane regions, without the hallmarks of amino acid conservation or predicted structural conservation that would be expected for an enzyme. Overexpression of TM3 alone disturbs intracellular membrane trafficking (Cottam et al, 2011(Cottam et al, , 2014, resulting in an accumulation of singlemembrane vesicles around the microtubule organization complex (Angelini et al, 2013). However, quantitative electron microscopy revealed that expression of TM2 with TM3 prevents the membrane disruption seen with TM3 expression alone (Angelini et al, 2013).…”
Section: Viral Proteins Involved In Organelle Formationmentioning
confidence: 99%
“…This effect was also described for nsp6 of MHV and SARS-CoV, as well as the arteriviral PRRSV nsp5-7 (Cottam et al, 2011). The autophagosomes induced by these proteins appeared to be smaller in size than normal autophagosomes, as judged from light-microscopy images, and therefore closer to viral DMVs (Cottam et al, 2014). However, in contrast with individually expressed nsp6, IBV infection did not induce LC3 relocalization and autophagic signalling in avian cells (Maier et al, 2013a).…”
Section: A Link With Autophagy?mentioning
confidence: 52%
“…However, when compared to the properties of starvation-induced autophagosomes, those generated by Coronavirus infection or NSP6 proteins presented significant differences. NSP6-induced autophagosomes displayed limited ability to undergo expansion, preventing formation of large autolysosomes, and hence circumvented degradation of viral particles through the lysosomal pathway [43]. Results obtained with IBV, SARS and MHV nsp6 was recapitulated with Middle eastern respiratory syndrome coronavirus (MERS-CoV), where a similar phenomenon was observed for nsp6 [44].…”
Section: Partial/selective Autophagymentioning
confidence: 73%
“…Infectious bronchitis virus (IBV) -an avian coronavirus responsible for major losses to the poultry industry, is one such example where a significant portion of the genome encodes nonstructural proteins (NSP) dedicated to virus replication. Expression of NSP6 proteins resulted in increased levels of Ptdlns3P on ER membranes, recruitment of Ptdlns3P effector protein WIPI2 and the generation of autophagosomes directly from the ER [42,43]. However, when compared to the properties of starvation-induced autophagosomes, those generated by Coronavirus infection or NSP6 proteins presented significant differences.…”
Section: Partial/selective Autophagymentioning
confidence: 97%